The complexation of neptunium(V) with fluoride at elevated temperatures: Speciation and thermodynamics. (May 2019) - Maiwald, Martin M.; Fellhauer, David; Skerencak-Frech, Andrej; Panak, Petra J.
Abstract : The complexation of NpO2 + with fluoride is studied in aqueous solution using Vis/NIR absorption spectroscopy. The total ligand concentration (NaF), ionic strength (NaClO4 ), and temperature (T = 20–85 °C) is varied, yielding detailed information on the thermodynamics of the complexation reaction. Two distinct complex species (NpO2 Fn 1−n, n = 1, 2) are identified by peak deconvolution of the absorption spectra. At 20 °C and Im = 1.0 the absorption band of NpO2 F is located at 983.8 ± 0.2 nm. The absorption band of the NpO2 F2 − complex is located at 988.4 ± 0.2 nm. With increasing temperature and ionic strength the chemical equilibrium of the complexation reaction shifts towards the complexed Np(V) species. The conditional stability constants log β'n (T) are calculated according to the law of mass action and are extrapolated to Im = 0 for each temperature with the specific ion interaction theory (SIT). The determined log β 0 n (T) values increase by 0.2–0.6 in the studied temperature range. Furthermore, the log β 0 n (T) values correlate linearly with the reciprocal temperature and fitting the data according to the integrated Van't Hoff equation yields the standard reaction enthalpies (Δr H 0 m ) and entropies (Δr S 0 m ). The reactions are endothermic and are solely driven by the high gain of entropy. In addition, the binary SIT ion-ion interaction coefficient εj, k of the respective complex species are determined. Highlights: Chemistry of actinides. Complexation of Np(V) with F - . Thermodynamic functions: log β 0 (T), Δr H 0 m, Δr S 0 m . Spectroscopy at elevated temperatures.